2011
DOI: 10.3844/jssp.2011.190.198
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in E-Commerce on the Basis of Online Retailing

Abstract: Problem statement:The rapid spread of e-commerce has created tremendous opportunities for economic efficiency and customer choice. Use of the global Internet computer network for ecommerce activities provides some advantages to the consumers on their daily life. On the other hand Internet represents a new environment for unethical behavior. While e-commerce has witnessed extensive growth in last decade, consumers concerns regarding ethical issues also continue to increase. Even many consumers and businesses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Many researchers have applied the fuzzy theory and AHP to solve the focused problems (Sujatha and Santhanam, 2010). Numerous researchers have focus on the issue of website, database, learning theory and EC (Rjoub et al, 2009;Sundaram et al, 2010;Erikson and Carifio, 2009;Igau et al, 2011;Nardal and Sahin, 2011) In the research field of supply chain performance management, many researchers have involved in the relevant subjects. Lee et al (2001) investigated supply chain management from the perspective of manufacturer management.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have applied the fuzzy theory and AHP to solve the focused problems (Sujatha and Santhanam, 2010). Numerous researchers have focus on the issue of website, database, learning theory and EC (Rjoub et al, 2009;Sundaram et al, 2010;Erikson and Carifio, 2009;Igau et al, 2011;Nardal and Sahin, 2011) In the research field of supply chain performance management, many researchers have involved in the relevant subjects. Lee et al (2001) investigated supply chain management from the perspective of manufacturer management.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature of WSN, Priority and Random Selection for Dynamic Window Secured Implicit techniques (Hanapi et al, 2009), Optimal Power Multicast (Maalla et al, 2009), Low Power Phase Locked Loop Frequency Synthesizer (Ismail and Othman, 2009), Transportation Infrastructural Health (Chang and Mehta, 2010), Ethical Issues in ECommerce (Nardal and Sahin, 2011) are available resources for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…It refers to a retailer's ability to honour the promises made on the website. For example, the price shown on an e-tailing website should match the price consumers actually pay (Nardal and Sahin, 2011). Research by Roman (2007) found that fulfilment is a key dimension that influences consumer perceptions of online retailing service quality.…”
Section: Relationships Between Ethical Factors and Website Credibilitymentioning
confidence: 99%
“…Deception refers to business practices that defraud or mislead consumers, and the actions of retailers that take advantage of customers (Nardal and Sahin, 2011;Roman, 2007). Deception is an especially important component associated with online commerce sites because the shopper usually cannot engage in face-to-face contact with the seller; therefore consumers may be more likely to be subject to deception while shopping online (Grazioli and Jarvenpaa, 2000).…”
Section: Relationships Between Ethical Factors and Website Credibilitymentioning
confidence: 99%